Molecular dynamics simulation of temperature and concentration distribution at liquid-gas interface during liquid air storage process - Zhanping You; Menghan Cheng; Changjie Ma; Yufei Xiao; Xuemin Zhao; Camila Barreneche; Xiaohui She (Energy and Built Environment)
To address global challenge of climate changes, renewable energy has been fully developed in recent years. However, renewable energy is usually intermittent which makes it challenging for application. Liquid air energy storage can effectively store intermittent energy with promising prospects. Liquid air is a mixture composed of N2, O2 and Ar with different evaporation temperatures. It is assumed to form temperature and concentration stratification during storage and thus causes safety challenge. To address this issue, molecular dynamics (MD) simulation method is used to study the temperature and concentration distribution characteristics in liquid air. The results show that the system temperature remains constant at 94 K with no temperature stratification during storage. However, the concentration of liquid air changes along vertical direction (z axis): the oxygen concentration remains stable around 21 % as z is 0–60 Å, rises to 22.1 % as z is from 60 to 70 Å and drops to 0 % as z is above 80 Å. The thin and short stratification phenomenon occurs at the gas-liquid interface region. In addition, a higher heat flux leads to a higher evaporation rate and a larger oxygen concentration. As the heat flux increases from 0.0 to 2.4 W/m2, evaporation rate rises from 0.13 to 0.2 % and the oxygen concentration at the liquid-gas interface reaches 22.3 %. Thus, concentration stratification exists during liquid air storage and should be treated carefully. This paper provides an insight into the temperature and concentration distribution of liquid air during storage and is significant for safety improvement and development of liquid air energy storage.